Economy, Necessity, Political Realitry: Two Planning Efforts in Kitchener-Waterloo, 1912-1925 - Bloomfield, Elizabeth (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
Between 1912 and 1925, the Ontario communities of Kitchener and Waterloo experienced two distinct phases of city planning ideas and proposals. The second phase, in which Thomas Adams and Horace Seymour were the professional planners, led to the adoption of Canada's first urban zoning by-law. Stages in the planning process have been reconstructed, mainly from research in records of the municipal councils and boards of trade and from the daily newspapers. The emphasis is on local perceptions of planning, planning as an issue in local politics and the interaction between outside planners and the local community. Themes include the significance of key individuals and the press in leading public opinion, the reluctance of municipal councils to antagonize the voters, and recurrent suspicions of the motives of those who advocated planning. The case-study also illustrates the diffusion of ideas about planning, as of other aspects of urban reform, from large metropolitan centres to smaller cities, and the transition in these derived concepts from "City Beautiful" ideals to political realistic type of plan.